The answer would be 362 miles
add the number of miles from day one and day two
If you would like to calculate 6/(x+1)-5/2=6/(3x+3), you can do this using the following steps:
6/(x+1)-5/2=6/(3x+3)
6/(x+1)-5/2=6/(3(x+1)) /*(x+1)
6 - 5/2 * (x+1) = 6/3
6 - 2 = 5/2 * (x+1)
4 = 5/2 * (x+1) /*2/5
4 * 2/5 = x + 1
8/5 - 1 = x
x = 8/5 - 5/5 = 3/5
The correct result would be 3/5.
Complementary I’m sure but I could be wrong
Answer:
42x -27
Step-by-step explanation:
we apply distributive property:
7(6x – 4) + 1
7*6x - 7*4 +1
42x - 28 +1
42x -27
The answer is3000.Hope it helps